Commodifying postsocialist cinema: filmmakers and the privatization of the Polish and Czech film industry after 1989. (2nd January 2022) - Pehe, Veronika
ABSTRACT: The state's efforts at privatization after the collapse of communist regimes in Eastern Europe often met with disapproval from cultural producers, who worried that their form of cultural production (often understood by them as "art" rather than "commodity") required state patronage to survive. This paper examines the case of cinema in the Czech Republic and Poland. Using contemporary press sources, it traces how filmmakers responded to the new prominence of commercial cinema and their often-perceived loss of prestige and status of "autonomous artists". Both the creative outputs and the discourse of filmmakers illustrate the changing values attached to the free market and to the purpose of cultural production in a market economy during transformation. Following a generational story, the paper establishes similarities between the discourse of different age groups of filmmakers in both countries; but at the same time, it accounts for the diverging acceptance of marketization by outlining country-specific differences: filmmakers searched for a language to critique or to affirm the transformation, their stance largely dependent on the extent to which they worked with inherited modes from the late socialist era, specific cultural traditions, and the financial conditions in which they operated.